Thermal activation of regenerated fiber Bragg grating in few mode fibers - Lai, M.H.; Gunawardena, D.S.; Lim, Kok Sing; Machavaram, V.R.; Lee, S.H.; Chong, W.Y.; Lee, Y.S.; Ahmad, Harith (Elsevier, 2016)
This work demonstrated for the first time, the thermal regeneration of two and four modes graded index fiber Bragg gratings using high temperature tube furnace. During the regeneration process, the seed grating is erased and a new grating with lower index contrast is formed. The thermal calibration shows that the temperature sensitivity of regenerated grating is slightly higher for fiber with larger core. On the other hand, the regeneration temperature is lower for fiber with smaller core. The temperature sustainability up to 900 °C is observed for the produced regenerated gratings in few mode fibers.